Induction chemotherapy for locally advanced laryngeal and hypopharyngeal cancer: Single institution experience. Issue 11 (16th July 2020) - Dagan, Or; Moore, Assaf; Nachalon, Yuval; Alkan, Uri; Biadsee, Ameen; Shochat, Isaac; Popovtzer, Aron
Abstract: Background: The role of induction chemotherapy (IC) in locally‐advanced head and neck squamous cell carcinoma (LAHNSCC) is unclear. Methods: A retrospective study of 104 patients with LAHNSCC of the larynx and hypopharynx, treated with IC or up‐front chemoradiotherapy (CRT). Results: Eighty patients received CRT and 24 IC followed by CRT; median follow up was 51.33 months. IC significantly improved median overall survival (OS) in the hypopharyngeal cancer group (64.7 vs 21 months, P = .003); with significant difference in the proportion of complete response at first imaging assessment post definitive CRT; no significant difference in disease free survival (DFS), loco‐regional or distant failure in the hypopharyngeal cancer group; or OS and DFS in the laryngeal cancer group. Patients with laryngeal cancer had significantly better median OS than those with hypopharyngeal cancer. Conclusions: IC significantly improved complete response rates after CRT, and improved outcomes for patients with locally advanced hypopharyngeal, not laryngeal, cancers.